Sociological Analysis of Transformations in the Family Structure in Iran over the Past Five Decades (1966-2016) and Prediction of Its Future Trends - Mohammad Taghi Sabzehei; Milad Bagi; Mohammad Mobaraki; Javad Afsharkohan (Strategic Research on Social Problems)
IntroductionSocial theorists assert that the family is one of the primary social institutions undergoing significant transformation due to modernization in recent decades, both globally and specifically in Iran. Iranian sociologists observe the emergence of what they term the "modern family" coinciding with a decline in patriarchal structures. There is a gradual transition from extended to nuclear family arrangements accompanied by a steady decrease in population growth as fertility rates decline. Numerous studies and reports reveal a consistent upward trend in divorce rates across Iran, highlighting another significant shift within Iranian families. Additionally, the rise of "white marriages"—cohabitation without formal marriage—poses a fundamental challenge to traditional family structures. Experts in family studies also note the increasing prevalence of alternative family forms, such as cohabitation. These data, along with other evidence that will be analyzed in the subsequent sections of this article, indicates the emergence of structural changes within the institution of the Iranian family. Exploring the dimensions of these transformations offers critical insights into the broader dynamics of Iranian society.  Materials and MethodsThis study employed a mixed-methods approach, integrating both quantitative and qualitative analyses to investigate transformations in the family structure in Iran over the past five decades (1966-2016). The research was structured around several key dimensions: family size, household composition, divorce rates, marriage patterns, and socioeconomic indicators, particularly focusing on women's roles.The quantitative data included census data and fertility and divorce rates. To gather the census data, statistical data were sourced from the Iranian Statistical Center, including population censuses conducted in 1966, 1976, 1986, 1996, 2006, and 2016. The key metrics extracted included average family size, proportions of nuclear versus extended family households, single-person households, and the demographic composition of households (e.g., female-headed households). National data on fertility and divorce rates were collected from governmental and academic reports to analyze trends over the specified period.The qualitative data encompassed interviews and focus groups and literature review. Semi-structured interviews and focus group discussions were conducted with sociologists, experts of family studies, and individuals from diverse family backgrounds. The aim was to gather insights into personal experiences and perceptions of family transformations, including the rise of cohabitation and changing marital norms. In addition, a comprehensive review of existing literature on family structures in Iran was undertaken to contextualize quantitative findings and identify gaps in previous research.To conduct the statistical analysis, descriptive statistics were employed to summarize demographic changes, including trends in family size, age at marriage, and divorce rates. Comparative analyses were conducted to highlight differences across decades. Furthermore, regression analysis was utilized to assess relationships between socioeconomic indicators (e.g., women’s labor force participation and literacy rates) and changes in family structures. Afterwards, qualitative data from interviews and focus groups were analyzed by using thematic analysis to identify recurring themes related to individualism, changing family dynamics, and the impact of modernization on family structures. Discussion of Results & ConclusionAccording to the theories of many sociologists, changes, such as the rise of single-parent families, cohabitation, emergence of new family structures, population aging, and declining fertility rates are the phenomena that are either already occurring or likely to occur in families worldwide. Many of these characteristics are evident in contemporary Iranian families. However, the trajectory of family transformation in Iran diverges from that of families in the West and globally in two key areas: (a) cohabitation and (b) same-sex family structures.In Iran, most marriages no longer adhere to traditional patterns based on familial or communal considerations. Instead, they are increasingly based on individual love and personal choice. This shift aligns with theories proposed by scholars, such as Beck, Giddens, Castells, Chill, and Papino, who emphasize the growth of individualism as a consequence of modernization. Individualism accounts for many structural changes in Iranian families, including the rise in single living, increased divorce rates, higher average ages at marriage, and declining fertility rates.The overall findings of this study suggested that changes in socioeconomic indicators related to women had significantly contributed to these transformations. Despite the dominance of a religious government and the pervasive influence of religion on family institutions in Iran, divorce rates and marriage ages have continued to rise, while fertility rates have declined in recent years. Predictions indicated that the trajectory of structural changes in Iranian families would increasingly align with global family transformation trends as a result of globalization, a conclusion that was supported by other domestic studies.